2018
DOI: 10.1158/1535-7163.mct-17-1178
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of ERBB2/ERBB3 for the Treatment of SLC3A2-NRG1–Mediated Lung Cancer

Abstract: We characterized the fusion gene in non-small cell lung cancer (NSCLC) and established an effective therapy for patients with SLC3A2-NRG1 fusion-positive cancer. The SLC3A2-NRG1 fusion product was composed of the SLC3A2 transmembrane domain and the EGF-like domain of the neuregulin 1 (NRG1) protein. The NRG1 family is classified as a ligand of the ERBB family. We identified ERBB3 and ERBB4 in the ERBB family as binding partners of the SLC3A2-NRG1 fusion protein via ligand and receptor binding assays. We confir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…As NRG1 alterations activate the ERBB2/ERBB3 signaling pathway, targeted treatment with inhibitors of this pathway is an appealing therapeutic strategy. Dual targeting of ERBB2 and ERBB3 has also been evaluated in preclinical models (22,23). Afatinib, a pan-ERBB inhibitor, was successfully utilized in this manner, and several patients with tumor harboring an NRG1 fusion achieved durable benefit with afatinib (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…As NRG1 alterations activate the ERBB2/ERBB3 signaling pathway, targeted treatment with inhibitors of this pathway is an appealing therapeutic strategy. Dual targeting of ERBB2 and ERBB3 has also been evaluated in preclinical models (22,23). Afatinib, a pan-ERBB inhibitor, was successfully utilized in this manner, and several patients with tumor harboring an NRG1 fusion achieved durable benefit with afatinib (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that, in contrast to aforementioned case reports of afatinib, some of these patients experienced progressive disease following afatinib monotherapy (Table 1). Notably, an in vitro study using afatinib, pertuzumab (anti-ERBB2 mAb), and lumretuzumab against an SLC3A2-NRG1 fusion model reported that the combination treatment with two mAbs or the combination treatment of one of the drugs plus taxol was more effective than each of the single agents alone (45). These in vitro studies will be important to evaluate the effectiveness of potential treatment strategies, although the results should be confirmed in clinical settings.…”
Section: Nrg1 Fusionsmentioning
confidence: 99%
“…Promote cell mitosis, regulate cell proliferation, differentiation, migration and tumor formation[52,53]. ERBB2 is overexpressed to varying degrees in various malignancies such as breast cancer[54], ovarian cancer[55], non-small cell lung cancer[56], gastric cancer[57], and etc.. ERBB3 / ERBB2 dimer is the most active ERBB dimer in ERBB dimer, which can activate PI3K/AKT Jak/Stat and other signaling pathways, regulate cell proliferation, differentiation, migration and other activities[58].ERBB3 is closely related to the occurrence and development of various tumors. Abnormal activation and overexpression of the HER3 gene can be seen in malignant tumors such as breast cancer[59], gastric cancer[60], ovarian cancer[61], prostate cancer[62], and etc.. After binding ERBB4 with ligands (neurodifferentiation factor heparin binding epidermal growth factor, etc.…”
mentioning
confidence: 99%